Growth, Biomass Production And Nodulation In Acacia nilotica (l.) Willd. Ex Del. Seedlings As Influenced By Inorganic And Biofertilizers - Singh, Manwindra; Garg, Rakesh K.; Singh, Avtar (Indian Forester, 2024)
With the aim to produce quality planting stock with minimum use of chemical fertilizers, an experiment was conducted to study the effect of inorganic and biofertilizers, alone and in combination, on growth, biomass and nodulation in Acacia nilotica, a very important leguminous tree species for rural livelihood. The treatments comprised of all possible thirty-six combinations of three levels of nitrogen (0, 30 and 60 kg N ha-1), three levels of phosphorus (0, 75 and 150 kg P2O5 ha-1) and four biofertilizers levels (No biofertilizer, VAM fungi, Rhizobium and VAM fungi + Rhizobium). The experiment was established in factorial split plot design with nine combinations of N and P in the main-plot and four bio-fertilizer levels in the sub plots with three replications. Seedlings inoculated with VAM fungi and Rhizobium, individually or in combination, resulted in higher growth, shoot and root biomass and nodulation as compared to uninoculated and unfertilized seedlings. Among different doses of nitrogen and phosphorus, when applied individually, 30 kg N and 75 kg P2O5 ha-1 resulted in higher growth and biomass production of roots and shoots. Dual inoculation of VAM fungi and Rhizobium supplemented with 30 kg N and 75 kg P2O5 ha-1 resulted in maximum biomass and growth.